Mechanistic insights on anserine hydrolyzing activities of human carnosinases - Pandya, Vaibhav Kumar; Shankar, S. Shiva; Rajesh, S.; Rathore, Rajeshwari; Kumaran, Sangaralingam; Kulkarni, Mahesh J. (Biochemica ET Biophysica Acta- General Subjects, 2023)
Anserine and carnosine represent histidine-containing dipeptides that exert a pluripotent protective effect on human physiology. Anserine is known to protect against oxidative stress in diabetes and cardiovascular diseases. Human carnosinases (CN1 and CN2) are dipeptidases involved in the homeostasis of carnosine. In poikilothermic vertebrates, the anserinase enzyme is responsible for hydrolyzing anserine. However, there is no specific anserine hydrolyzing enzyme present in humans. In this study, we have systematically investigated the anserine hydrolyzing activity of human CN1 and CN2. A targeted multiple reaction monitoring (MRM) based approach was employed for studying the enzyme kinetics of CN1 and CN2 using carnosine and anserine as substrates. Surprisingly, both CN1 and CN2 can hydrolyze anserine effectively. The observed catalytic turnover rate (Vmax/[E]t) was 21.6 s-1 and 2.8 s-1 for CN1 and CN2, respectively. CN1 is almost eight-fold more efficient in hydrolyzing anserine compared to CN2, which is comparable to the efficiency of the carnosine hydrolyzing activity of CN2. The Michaelis constant (Km) value for CN1 (1.96 mM) is almost three-fold lower compared to CN2 (6.33 mM), representing higher substrate affinity for anserine-CN1 interactions. Molecular docking studies showed that anserine binds at the catalytic site of the carnosinases with an affinity similar to carnosine. Overall, the present study elucidated the inherent promiscuity of human carnosinases in hydrolyzing anserine using a sensitive LCMS/MS approach.
Keywords: Anserine; Carnosinase; Carnosine; Diabetes; LC-MS; MS; Multiple reaction monitoring (MRM); Promiscuity

De novo structure prediction of meteorin and meteorin-like protein for identification of domains, functional receptor binding regions, and their high-risk missense variants - Shankar, S. Shiva; Banarjee, Reema; Jathar, Swaraj M.; Rajesh, S.; Ramasamy, Sureshkumar; Kulkarni, Mahesh J. (Journal of Biomolecular Structure & Dynamics, 2024)
Meteorin (Metrn) and Meteorin-like (Metrnl) are homologous secreted proteins involved in neural development and metabolic regulation. In this study, we have performed de novo structure prediction and analysis of both Metrn and Metrnl using Alphafold2 (AF2) and RoseTTAfold (RF). Based on the domain and structural homology analysis of the predicted structures, we have identified that these proteins are composed of two functional domains, a CUB domain and an NTR domain, connected by a hinge/loop region. We have identified the receptor binding regions of Metrn and Metrnl using the machine-learning tools ScanNet and Masif. These were further validated by docking Metrnl with its reported KIT receptor, thus establishing the role of each domain in the receptor interaction. Also, we have studied the effect of non-synonymous SNPs on the structure and function of these proteins using an array of bioinformatics tools and selected 16 missense variants in Metrn and 10 in Metrnl that can affect the protein stability. This is the first study to comprehensively characterize the functional domains of Metrn and Metrnl at their structural level and identify the functional domains, and protein binding regions. This study also highlights the interaction mechanism of the KIT receptor and Metrnl. The predicted deleterious SNPs will allow further understanding of the role of these variants in modulating the plasma levels of these proteins in disease conditions such as diabetes.
Keywords: domains; Meteorin; meteorin-like; missense variants; protein-protein interactions; structure prediction

Simple freeze-thaw based method for efficient purification of recombinant human proinsulin from inclusion bodies - Rajesh, S.; Jathar, Swaraj; Banarjee, Reema; Sharma, Monika; Palkar, Shivani; Shankar, S. Shiva; Kulkarni, Mahesh J. (Protein Expression and Purification, 2025)
Insulin is a pivotal peptide hormone essential for regulating glucose homeostasis. It has been known for over 100 years, but its production and purification methods are still under improvement. Escherichia coli based bacterial expression system is primarily used for insulin production. The human insulin protein expressed in bacteria usually forms inclusion bodies, complicating the purification process. Traditionally, insulin purification is a timeconsuming process involving urea-based denaturation methods, and various refolding techniques, followed by extensive chromatographic methods. Here, we report an easy and efficient purification of human proinsulin involving freeze-thaw based solubilization method. The extracted proinsulin inclusion bodies are treated with different concentrations of urea, followed by a freeze-thaw based solubilization. The freezing was carried out at various temperatures, mainly -80 degrees C, -20 degrees C, and -196 degrees C to determine the optimum condition for solubilization. Highest solubilization of proinsulin from the inclusion body was achieved with 0.5M urea and -20 degrees C. Further Nickel NTA-based purification was performed, and the purified protein was characterized for disulfide mapping by high-resolution mass spectrometer (HRMS). We also performed glucose uptake assays to validate the functional properties of purified proinsulin. This freeze-thaw based mild solubilization approach is a fast and effective method for getting bioactive proinsulin, which will help further design better purification and processing strategies for insulin production.
Keywords: Diabetes; Disulfide mapping; glucose; insulin; Mass spectrometry